ISOLATION AND OPTIMIZATION OF ENVIRONMENTAL PARAMETERS (pH, LIGHT INTENSITY, AND TEMPERATURE) OF Spirulina sp. CULTURE UNDER LABORATORY CONDITION - RAHAYU (NIM 20605001), WINDY
Microalgae, especially Spirulina has important role in aquaculture. It also has been known as a food source for human for centuries due to its nutritional aspects such as protein, vitamin, carotenoid pigment, lipid, and polysaccharide. Spirulina also used for animal feed and in cosmetic industries. Mass culture of Spirulina became an important aspect for many microalgae producers to full fill the market needs. Isolation technique in order to have a good strain of Spirulina and also optimum culture condition were important factors in mass culture. Therefore, the objectives of this study were to isolate Spirulina from natural environment and to obtain the optimum environmental condition as pH, light intensity and temperature in Spirulina culture under laboratory condition. There were three isolation method that have been used in this study (pour, streak and pipetting), but only pipetting method succeeded to obtain Spirulina. Spirulina was collected from Saguling reservoir area at Cihampelas village, West Java. The optimization was conducted by using single variable method. For each parameter, there were three kinds of variation, as for pH, 9, 10 and 11; light intensity 2500, 3500 and 4500 lux; and temperature 28, 31, 33oC. All experiments was conducted in five replicates. The growth of Spirulina sp. was measured by several parameters of growth such as cell density (cell/mL) with microscopic examination, growth rate (ro) and carrying capacity (K). Each parameter was analyzed statistically by one-way ANOVA and Duncan posthoc test. The result showed that under different pH, the highest cell density was obtained in pH 10 (2,82 x 105 cell mL-1) at the 22nd day. The lowest cell density was obtained in pH 11(2,33 x 105 cell mL-1). The highest carrying capacity was obtained in pH 10 (3,09 x 105 cell mL-1) and the lowest in pH 11 (and 2,66 x 105 cell mL-1 ). pH 10 has the lowest specific growth rate (3,060 x 103 cell mL-1 day-1) and the highest was obtained in pH 9 (3,361 x 103 cell mL-1 day-1). Under different condition of light intensity, the experiment showed that the highest cell density was obatain in 3500 lux (3,90 x 105 cell mL-1) and the lowest in 2500 lux (2,36 x 105 cell mL-1) at the 21st day. The highest carrying capacity was obtained in 3500 lux (3,96 x 105 cell mL-1) and the lowest in 2500 lux (3,43 x 105 cell mL-1). The lowest and spesifik growth rate was obtained in 4500 lux (3,643 x 103 cell mL-1 day-1) and the highest was obtained in 2500 lux (3,920 x 103 cell mL-1 day-1). The highest cell density was obtained in 33oC (1,63 x 105 cell mL-1 ) and the lowest in 28oC (1,39 x 105 cell mL-1 ) at the 15th day. The highest carrying capacity was obtained in 33oC (2,08 x 105 cell mL-1) and the lowest in 28oC (1,63 x 105 cell mL-1 ). The highest specific growth rate was obtained in 31oC (3,758 x 103 cell mL-1 day-1) and the lowest in 33oC (3,595 x 103 cell mL-1 day-1). These results showed that Spirulina sp. could be isolated from natural environment by pipetting method and could be cultured under laboratory condition with the optimal environmental parameters of pH 10, light intensity 3500- lux and temperature 33oC in 22 day culture periods.